We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
63
1
avatar

\(a^log_ab=b\)

 

a^log_ab=b

Saw it in a textbook (Revision) How does it work ? 

 Sep 16, 2019
 #1
avatar+104911 
+2

a^ ( loga b)    = b      (1)

 

I'll admit that when I first saw this in Algebra it was a little tough to see

 

Let's prove this is true :

 

Take the log of both sides

 

log a ^ (loga b)   = log b        and by a log property we have

 

( loga b) * log a  = log b        divide both sides by log a

 

loga b    = log b /log a         by the change-of-base rule for logs we can write

 

log b / log a   = log b  / log a

 

Since this is an identity....then so is  (1)

 

 

cool cool cool

 Sep 16, 2019
edited by CPhill  Sep 16, 2019

11 Online Users

avatar